PENGEMBANGAN BAHAN AJAR TEMATIK BERBASIS SCIENTIFIC UNTUK SISWA KELAS IV SD TEMA TEMPAT TINGGALKU SUB TEMA KEUNIKAN DAERAH TEMPAT TINGGALKU - Cintang, Nyai (Dinamika Jurnal Ilmiah Pendidikan Dasar, 2019)
Factual conditions require the development of teaching materials in thematic learning using a scientific approach to improve the available teaching materials. This study aims to: 1) examine the factual conditions for the use of teaching materials in thematic learning in the 2013 curriculum; 2) knowing the development of scientific based thematic teaching materials for fourth grade elementary students; 3) knowing expert judgment on the feasibility of scientific-based thematic teaching materials for fourth grade elementary students; 4) knowing the effect of the use of scientifically based thematic teaching materials on the learning achievement of fourth grade elementary school students; 5) knowing the teacher’s assessment of learning using thematically based thematic teaching materials for grade IV elementary school students; 6) knowing the response of students to learning using thematically based thematic teaching materials for fourth grade elementary school students. This study uses Development Research with qualitative and quantitative research designs. The development process uses the 4-D model of Thiagarajan, Semel and Semel which has been modified to be the stage of defining, designing, and developing. Teaching materials that have been validated by experts get the category of "very valid and without revision" from expert responses and teacher evaluations with agreed criteria, student responses to the use of teaching materials in learning get very good responses from students. The results of the trials using the experimental design The Before And After Design show that there is an effect of the use of scientifically based thematic teaching materials on the learning achievement of PPKn; 2) there is the influence of the use of scientifically based thematic teaching materials on social studies learning achievements; 3) there is the influence of the use of scientifically based thematic teaching materials on the learning achievement of science. Scientific based thematic teaching materials for Grade IV Primary School students can be used in learning.